ALKALOID : GOLONGAN SENYAWA DENGAN SEGUDANG MANFAAT FARMAKOLOGIS - Ardy Tanfil. T; Wiwin Alfianna; Ing Mayfa Br Situmorang (Poltekkes Kemenkes Medan, 2023)
ABSTRACT Alkaloids are a family of naturally occurring chemicals that can be found in a variety of plants, including certain plants used in medicine. They have been used in various forms of traditional medicine for thousands of years and are known to have a wide range of pharmacological effects on the human body. It has been shown that alkaloids may have potential therapeutic effects for various diseases and ailments. However, their use can also be associated with various side effects, and as a result, it is important to be careful when using them. This article presents many studies investigating the impact of alkaloids on living organisms. Keywords: Alkaloids, Pharmacology, Secondary Metabolites